Construir o construído - Projecto para uma casa burguesa na Rua do Almada - André de Azevedo Costa Gomes (2018)
The conception of a rehabilitation project for a Porto's bourgeois house in Rua do Almada, defines the fundamental subject that this work addresses. Starting from this design exercise, the dissertation focuses on the formulation of practical problems raised during the course of the design process, forming a space for critical thinking about the resolution of these same problems.Its designation of Building the built, verbalizes right away an intention, a project purpose that pretends to shape the existing, in order to contribute to the juxtaposition of the layers of time only perceivable in its whole. Building the built is to recognise that we work with cities of the past, knowing that it is with that memory that one should build the present.It's in this regard that the house's facade emerges as a key subject between the two essential topics for the construction of the project - the city and the house -, between what happens in and out of this element.